2008
DOI: 10.4103/0970-1591.40616
|View full text |Cite
|
Sign up to set email alerts
|

The role of flaps and grafts in modern hypospadiology

Abstract: The modern hypospadiologist must be proficient in the use of both vascularized flaps and free grafts. When choosing a repair for any given patient with hypospadias, one must consider the length of the urethroplasty, the presence and degree of ventral curvature and perhaps most importantly, the surgeon’s own experience. Not all repairs are created equally and different complication rates and cosmetic outcomes can be seen among different surgeons utilizing the same technique. Each surgeon tends to infuse their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…reported fistula rates ranging from 6% to 20% using the onlay procedure. [ 4 14 17 19 ] Our study found that the incidence of urethrocutaneous fistulas using the modified method was only 10%, n = 3) which is in line with the lower ranges reported by the literature. Moreover, our study had a 10% rate of glanular dehiscence, and a 3.3% rate of diverticula following surgery.…”
Section: Discussionsupporting
confidence: 88%
“…reported fistula rates ranging from 6% to 20% using the onlay procedure. [ 4 14 17 19 ] Our study found that the incidence of urethrocutaneous fistulas using the modified method was only 10%, n = 3) which is in line with the lower ranges reported by the literature. Moreover, our study had a 10% rate of glanular dehiscence, and a 3.3% rate of diverticula following surgery.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our research found that on the premise of the anesthetic safety, hypospadias repairing operation is feasible in some selective cases in neonate [12]. As the major operation method for hypospadias with preservation of urethral plate, the TIP method is applicable to the therapy of most distal hypospadias and few proximal hypospadias [8]. We found that the correction effect of the Mathieu method for clubbed penis in coronary sulcus type hypospadias (type I/IIa) with clubbed penis was better than that of TIP method, and the Onlay method may be used as a supplement to TIP method in the operative repair for Hypospadias (type II/III) with clubbed penis over 45 degree or width of urethral plate less than 8 mm.…”
Section: Discussionmentioning
confidence: 80%
“…If the rebuilt urethra is less than 8F, it means that the urethral groove of urethral plate will be superficial, narrow and lacking of elasticity and the occurrence rate of post-operation complication such as urethral fistula and urethral stricture will be higher than other with rebuilt urethra over 10F. According to the reports of Sarhan et al [8], patients with urethral plate over 8mm who choose TIP can obviously increase the rate of success of operation, indicating that in the operative treatment for hypospadias, the cognition of operators to the morphological and histological characteristics of urethral plate and the selection of operation method have significant meanings to the increase of rate of success of operation. Some researchers found that grafted the raw area of the urethral plate with inner preputial skin in children with primary hypospadias during TIP improved the results of the operation which resulted in a significantly smaller number of unsatisfactory results, and particularly fewer cases of neourethral stenosis [9].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of hypospadias reconstruction is to restore normal penile voiding and sexual function. Several techniques have been described to correct hypospadias [2,10]. Tubularized incisional plate urethroplasty has gained widespread acceptance worldwide [10], but for proximal hypospadias or revisional procedures, no single surgical technique provides reliable outcomes due to the complexity these procedures entail.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been described to correct hypospadias [2,10]. Tubularized incisional plate urethroplasty has gained widespread acceptance worldwide [10], but for proximal hypospadias or revisional procedures, no single surgical technique provides reliable outcomes due to the complexity these procedures entail. Local, skin, or mucosal grafts are often required to provide additional tissue for restoring urethral continuity, for ventral lengthening, or for skin coverage.…”
Section: Discussionmentioning
confidence: 99%